THE EFFECTIVENESS OF TEACHING PHYSICS IN GRADE 7 THROUGH MATHEMATICAL APPROACHES - Sharibayev , Nosir; Saidvaliyev , Mirjalol (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
The paper substantiates the didactic effectiveness of mathematical approaches when teaching Grade 7 kinematics (distance, time, speed, average speed). The proposed core includes unit normalization, proportional reasoning, segmenting motion into stages, and an explicit problem-solving algorithm. Through theoretical analysis, lesson design, and assessment criteria, the study explains how these tools improve conceptual understanding, reduce common errors, and support independent problem solving. One representative problem is analyzed to illustrate how the method works in practice, and measurable indicators are suggested for learning diagnostics.